The influence of mindfulness training on running economy and perceived flow under different attentional focus conditions – an intervention study. Issue 4 (4th July 2021) - Hill, Antje; Schücker, Linda; Wiese, Marvin; Hagemann, Norbert; Strauß, Bernd
ABSTRACT: Training of mindfulness has gained relevance in sports teaching present moment regulation that is crucial to athletic performance. This study examines the impact of mindfulness training on flow experience and running economy within four attentional foci. N = 16 trained runners (EG) attended an eight-week mindfulness programme. Before ( t 1 ) and after ( t 2 ) the programme, they ran on a treadmill at moderate intensity under four attention conditions (focus on internal body signals, external video, core component of the movement, control focus). N = 15 trained runners obtained the mindfulness programme after completing t 1 and t 2 (CG). t 1 and t 2 were compared to examine if mindfulness training (1) promotes flow and (2) leads to changes in running economy. Only for the EG, repeated measures ANOVA indicated increased flow from t1 to t2 ( F (1, 14) = 35.71, p = <.001, η p 2 ) as well as improved running economy for all attention conditions ( F (1, 13) = 4.99, p = .044, η p 2 = .28). This study shows benefits of practicing mindfulness on subjective (flow) and objective parameters (oxygen consumption) improving running performance.